Hear, Now, Today: Active Analysis for the working actor:A "special guest workshop" delivered at The S Word, Prague, 12 November 2022. Issue 1 (2nd January 2023) - Merlin, Bella
ABSTRACT: In November 2022, The S Word symposium was hosted at DAMU, Prague, under the title 'Stanislavsky's Last Words'. Bella Merlin conducted a practical workshop on the 'constant state of inner improvisation' that underpins Stanislavsky's final rehearsal practice, Active Analysis, along with the vital role of 'dynamic listening' between actors. This paper is an account of that workshop, writing in an autoethnographic style and taking the reader through the improvisations and exercises as if present at the workshop. Merlin notes her training in Active Analysis at the State Institute of Cinematography, Moscow, in the early 1990s and her book Beyond Stanislavsky: The Psycho-Physical Approach to Acting (NHB 2001) as arguably the first hands-on account of Active Analysis in the UK. The 'line of thought' (discovered through textual analysis) and the 'line of action' (discovered through improvisations) link together to create a production through the process of Active Analysis. Stanislavsky's tools of the 'six fundamental questions', 'grasp', 'objectives' (or problems and tasks), and the essential feeling of 'now, today, here' as the raw material for creating roles are explored, along with identifying the scene's main 'event' and uncovering a simple 'score of physical actions'. The dramatic dialogue used is an open scene from Dave Kost's Books of Sides II (Routledge 2017). The overarching tool for the workshop is obshcheniye : community or 'communion'.